Onset of vitiligo following targeted therapy for BRAF(V600E)-mutated melanoma: case report - Brugnara, Sonia (Drugs Context, 2019)
Systemic treatment for metastatic melanoma has advanced dramatically in recent years with an impressive increase in the rate of overall survival. The two main different strategies are targeted therapies (i.e. BRAF and MEK inhibitors) and immunotherapy with monoclonal antibodies against the immune checkpoint proteins programmed death-1 (PD-1) and cytotoxic T-lymphocyte antigen-4 (CTLA-4). Vitiligo often accompanies immunotherapy in melanoma patients and even correlates with tumor regression after checkpoint blockade. At present, a correlation between vitiligo onset and outcome from immunotherapy is acknowledged; however, evidence of a correlation between vitiligo and efficacy of combination-targeted therapy is lacking. We describe our experience in a patient who received dabrafenib and trametinib and developed vitiligo-like depigmentation after treatment cessation.